Ant colony optimization (ACO) in scheduling overlapping architectural design activities - Wang, Chen; Abdul-Rahman, Hamzah; Ch’ng, Wei See (Journal of Civil Engineering and Management, 2016)
The increasing complexity of architectural design works refers to the need for high quality design solutions for overlapping activities through a shorter time period. Conventional network analysis techniques such as CPM could only represent sequential processes yet it is unable to handle a process which contains iterations so that it leads to the occurrence of unwanted omission of logic or information links between design activities. Ant Colony Optimization emerged as an efficient metaheuristic technique for solving computational problems in finding good paths through graphs. This research aims to develop an ACO based Design Activity Scheduling model (ACO-DAS) for the scheduling of overlapping architectural design activities and to test the workability of ACO-DAS through a hypothetical run. From the computational results of both CPM and ACO methods, the determination of critical path using ACO-DAS model resulted in a design duration at 50 while that for CPM was as long as 78. The durations of architectural design activities have been significantly shortened by ACO-DAS. ACO-DAS results in shorter design completion time thus it deems more advanced than CPM.